2010
DOI: 10.2176/nmc.50.470
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Pial-Dural Arteriovenous Malformation in the Anterior Cranial Fossa -Two Case Reports-

Abstract: Most arteriovenous malformations (AVMs) associated with the meningeal artery in the anterior cranial fossa are the pure dural type, and mixed pial-dural AVMs are rare. Two types of mixed pial-dural AVM occur in the anterior cranial fossa according to the shunting point: one with the nidus in the brain parenchyma of the frontal lobe, and the other with the shunting point in the dura mater. We describe two patients with AVMs fed by the anterior ethmoidal arteries and the persistent primitive olfactory artery, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…The pathogenesis of mixed DPAVM is still controversial. The presence of abnormal communications between the pial and dural arteries in the embryonic stage may lead to the development of mixed DPAVM [6]. Venous hypertension secondary to sinus thrombosis is believed to be the primary mechanism responsible for the formation of DPAVM.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of mixed DPAVM is still controversial. The presence of abnormal communications between the pial and dural arteries in the embryonic stage may lead to the development of mixed DPAVM [6]. Venous hypertension secondary to sinus thrombosis is believed to be the primary mechanism responsible for the formation of DPAVM.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we observed some ECA branches in 3 patients (Table 1) to contribute to the leptomeningeal AVMs supply, that is, the middle meningeal and the occipital artery, respectively. Other authors found sporadically the same arteries as the accessory AVMs feeders [16,41], and very rarely some of the persistent primitive arteries in the dural region [28]. Some authors registered dural vascular connections with intraventricular AVMs [74].…”
Section: Anatomy Of Feeding Arteriesmentioning
confidence: 99%
“…The feeders originating from some other persistent embryonal vessels were seen extremely rarely, e.g. from the primitive olfactory or hypoglossal artery [28,50]. Finally, some AVMs feeders are associated with the arterial fenestration [71], and some others with the moyamoya vessels [3,49].…”
Section: Anatomy Of Feeding Arteriesmentioning
confidence: 99%
“…There is a high incidence of aneurysms associated with PPOA [43,44,47,48] Vascular anomalies also should be considered in the differential diagnosis of olfactory impairment. There are a variety of conditions which can cause olfactory impairment like rare aneurysms of PPOA [47] or arteriovenous fistulae involving the anterior ethmoidal arteries [49] or mixed pial-dural arteriovenous malformations that involve PPOA [50].…”
Section: Vascularizationmentioning
confidence: 99%